2008
DOI: 10.1002/cbdv.200890031
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Biological Investigation of Hymenocallis littoralisSalisb.

Abstract: A phytochemical investigation of the bulbs and flowers of Hymenocallis littoralis SALISB., cultivated in Egypt, was carried out, which resulted in the isolation of four alkaloids, lycorine (1), hippeastrine (2), 11-hydroxyvittatine (3), and (+)-8-O-demethylmaritidine (4), and of two flavonoids, quercetin 3'-O-glucoside (5), and rutin (6). The volatile constituents of the plant flowers were analyzed for the first time by GC/MS, which led to the identification of 26 known compounds (Table 1). Finally, the antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 28 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…As to date, one study reported for the antimicrobial activity of the H. littoralis plant (Abou-Donia et al, 2008). Conversely, he stated that, the petroleum extract of the H. littoralis flower extract does not show activity for C. albicans strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to date, one study reported for the antimicrobial activity of the H. littoralis plant (Abou-Donia et al, 2008). Conversely, he stated that, the petroleum extract of the H. littoralis flower extract does not show activity for C. albicans strain.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1920, there are several alkaloids that have been discovered from H. littoralis bulbs (Yew et al, 2010);such as littoraline, trazettine, omethyllycorinine, pretazettine, macronine, lycorine, homolycorine, lycorenine, hippeastrine, lycoramine, demethylmaritidine, haemanthamine, vittatine, and 5,6-dihydrobicolorine (Lweis, 1998), hippeastrine, 11-hydroxyvittatine and two flavonoids quercetin3'-Oglucoside and rutin were isolated (Abou-Donia et al, 2008). In addition, Abou-Donia and coworkers (2008) identified 26 known volatile constituents from H. littoralis flowers (Abou-Donia et al, 2008). The primarily isolated lycorine alkaloid from H. littoralis was proven to have antineoplastic, cytotoxicity and antiviral properties (Ioset et al, 2001;Yew et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Tannin possessed spasmolytic activity in smooth muscles cells, free radical scavenger and antioxidant. Flavonoids have antioxidant and antimicrobial properties while saponins are glycosides possessed antimicrobial and inhibit Na+ efflux, by blockage of the entrance of the Na+ out of the cell, reducing congestive heart failure 13,12 alkaloids have possessed analgesic, antisplasmodic and bactericidal activities, antioxidant and are useful in renal disorder 14,15 . The current investigation showed the presence of certain constituents in ethanolic extract of M. spicata and O. sanctum (O. gratissimum, O. tenuiflorum and Croton bonplandianus).…”
Section: Phytochemical Analysis Of Ocimum Sanctum Species and Mentha mentioning
confidence: 99%
“…For decades, many plants from the Amaryllidaceae plant family had been used as remedy for innumerable illnesses. As reviewed by Abou-Donia et al (2008), Hymenocallis salisb. genus was first phytochemically studied in 1920, which resulted in the isolation of lycorine.…”
Section: Introductionmentioning
confidence: 99%